Prospects of social welfare work in Hungary and in Hajdú-Bihar county - Verdó, György (Acta Agraria Debreceniensis, 2012)
The social care has been accompanying phenomenon of mankind from ancient times. An individual's social and economic processes that affect the lives basically forced the representatives of the powers to help those in need. The concepts used in social care today (equality, solidarity, etc.) have evolved over the centuries, shaped by political ideologies of the content. This wide range of people living in today's society for granted the fact that life is present in the social care system, which is necessary for security.